2020
DOI: 10.2147/opth.s242681
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long-Term Outcomes After Idiopathic Epiretinal Membrane Surgery</p>

Abstract: Purpose: To report anatomic and logMAR best-corrected visual acuity (BCVA) outcomes with long-term follow-up after pars-plana vitrectomy and epiretinal membrane peeling (PPV-MP). Design: A retrospective case-series. Participants: Patients with epiretinal membrane (ERM) who underwent PPV-MP performed by one surgeon. Methods: Best-corrected visual acuity (BCVA) was recorded as a logMAR preoperatively and, when available, at 1, 2, 3, 5, 8, 10 years after surgery. The integrity of outer retinal layers was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
2
11
1
Order By: Relevance
“…Other pre-operative clinical factors, including age, lens status (phakic or pseudophakic), and glaucoma history, were not signi cantly different. Previous studies have reported a correlation between pre-and post-operative BCVA [19,20], while others have not [4,20,21]. In this study, we did not nd a correlation between pre-and post-operative BCVA.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Other pre-operative clinical factors, including age, lens status (phakic or pseudophakic), and glaucoma history, were not signi cantly different. Previous studies have reported a correlation between pre-and post-operative BCVA [19,20], while others have not [4,20,21]. In this study, we did not nd a correlation between pre-and post-operative BCVA.…”
Section: Discussioncontrasting
confidence: 70%
“…Post-operative BCVA in patients with ERM demonstrated progressive improvement and maintained a stable BCVA thereafter. Within 1 year, poorer pre-operative BCVA improved with a large proportional magnitude [4]. We found a signi cant BCVA improvement comparing preand post-operative in DR and no-DR patients.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Previous studies on the outcomes of epiretinal membrane surgery have not reported outcome differences based on gender. 16 , 18 , 19 , 22 , 23 Given the statistical significance of the association between male gender and better postoperative BCVA in this study, it is less likely to be the result of statistical bias. One tentative explanation for the association is the possible innately better visual function of men: prior research investigating gender differences in visual perception has found that males performed significantly better than females in several key aspects of vision, including visual acuity and motion detection.…”
Section: Discussionmentioning
confidence: 80%
“…Surgery involves pars plana vitrectomy (PPV) with membrane peeling. It is known to improve the central retinal thickness and visual acuity when retinal traction and ERM-causing edema resolve after surgery [ 4 , 5 , 6 ]. However, information remains limited about long-term changes in choroidal thickness after vitrectomy.…”
Section: Introductionmentioning
confidence: 99%